The Effectiveness of Linga App on Vocabulary Mastery in Reading among Senior High School Students - Novi Nurul Islami (Retain: Journal of Research in English Language Teaching, 2025)
This quantitative study with pre-experimental design examines the differences in vocabulary mastery between students taught using Linga app and those taught without it. 36 senior high school students in 11th grade who receive additional English subject (Bahasa Inggris lintas minat) served as the participants of this experiment. Students' vocabulary mastery was tested using the vocabulary level test developed by Paul Nation and then updated by Webb et al. in 2017. To analyze the tests result, paired sample t-test was administered to find out the difference between the data. The results of the experiment indicate a significant difference in students' vocabulary mastery. This is proven by the result of the paired sample t-test with p-value <.001, it means that the difference between the pretest and posttest scores is statistically significant. Besides the paired sample t-test result, effects size calculation using Cohen's d revealed a moderate effect value for the group, with Cohen's d value of 0.822. In order to gain deeper insights of participants' experience, a post-experimental quantitative questionnaire consisting of 10 Likert scale items was administered. The result of the post-experiment questionnaire revealed that participants responded positively to the vocabulary learning application, indicating it was effective and user-friendly. The majority of participant expressed high levels of satisfaction with the app's features, particularly those supporting pronunciation, contextual word learning, and vocabulary training. Despite these findings, as there is currently limited prior research regarding the use of Linga app in English language learning, future studies are encouraged to expand on these findings with larger subjects or different language skills other than vocabulary.